The Oxford handbook of organizational paradox - Smith, Wendy K.; Lewis, Marianne W.; Jarzabkowski, Paula; Langley, Ann (Professor) (Oxford : Oxford University Press, 2017)
Organisations are rife with paradoxes, evident in persistent and interwoven tensions for example between stability and change, flexibility and control, diversity and inclusion, long term and short term, social and financial, learning and performing. This handbook investigates paradoxes across various organisational phenomena and levels of analysis.
Ad Fontes - Philosophical foundations of paradox research / Jonathan Schad -- Paradoxes of Organizational Identity / Marya L. Besharov, Garima Sharma -- Alternate prisms for pluralism and paradox in organizations / Mariline Comeau-Vallée, Jean-Louis Denis, Julie Maude Normandin, Marie-Christine Therrien -- Paradox in Positive Organizational Scholarship / Kim S. Cameron -- Managing normative tensions within and across organizations: What can the Economies of Worth and paradox frameworks learn from each other? / Jean-Pascal Gond, Christiane Demers, Valerie Michaud -- The role of irony and metaphor in working through paradox during organizational change / John Sillince, Ben Golant -- Reflections on the paradoxes of modernity: A conversation with James March / Richard John Badham -- Paradox at an inter-firm level: A coopetition lens / Maria Bengtsson, Tatbeeq Raza-Ullah -- Pathways to ambidexterity: A process perspective on the exploration-exploitation paradox / Sebastian Raisch, Alexander Zimmermann -- Navigating the paradoxes of sustainability / Jason Jay, Sara Soderstrom, Gabriel Grant -- The paradoxes of time in organizations / Natalie Slawinski, Tima Bansal -- Psychoanalytic theory, emotion and organizational paradox / Michael Jarrett, Russ Vince -- On organizational circularity: Vicious and virtuous circles in organizing / Hari Tsoukas, Miguel Pinha de Cuhna -- Tensions in managing human resources: Introducing a paradox framework and resarch agenda / Julia Brandl, Anne Keegan, Marcia Lensges -- Looking at creativity through a paradox lens: Deeper understanding and new insights / Ella Miron-Spektor, Miriam Erez -- "I am...I said": Paradoxical tensions of individual identity / Mathew Sheep, Glen E. Kreiner, Gail Fairhurst -- Paradox in Everyday Practice: Applying Practice-Theoretical Principles to Paradox / Jane Le, Rebecca Bednarek -- Methods of paradox / Costas Andriopoulos, Manto Gotsi --
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 1, 2017).
Keywords: Organizational sociology